Characteristics of atmospheric mercury deposition and size-fractionated particulate mercury in urban Nanjing, China - J. Zhu; T. Wang; R. Talbot; H. Mao; X. Yang; C. Fu; J. Sun; B. Zhuang; S. Li; Y. Han; M. Xie (Atmospheric Chemistry and Physics, 2014)
A comprehensive measurement study of mercury wet deposition and size-fractionated particulate mercury (HgP) concurrent with meteorological variables was conducted from June 2011 to February 2012 to evaluate the characteristics of mercury deposition and particulate mercury in urban Nanjing, China. The volume-weighted mean (VWM) concentration of mercury in rainwater was 52.9 ng L−1 with a range of 46.3–63.6 ng L−1. The wet deposition per unit area was averaged 56.5 μg m−2 over 9 months, which was lower than that in most Chinese cities, but much higher than annual deposition in urban North America and Japan. The wet deposition flux exhibited obvious seasonal variation strongly linked with the amount of precipitation. Wet deposition in summer contributed more than 80% to the total amount. A part of contribution to wet deposition of mercury from anthropogenic sources was evidenced by the association between wet deposition and sulfates, as well as nitrates in rainwater. The ions correlated most significantly with mercury were formate, calcium, and potassium, which suggested that natural sources including vegetation and resuspended soil should be considered as an important factor to affect the wet deposition of mercury in Nanjing. The average HgP concentration was 1.10 ± 0.57 ng m−3. A distinct seasonal distribution of HgP concentrations was found to be higher in winter as a result of an increase in the PM10 concentration. Overall, more than half of the HgP existed in the particle size range less than 2.1 μm. The highest concentration of HgP in coarse particles was observed in summer, while HgP in fine particles dominated in fall and winter. The size distribution of averaged mercury content in particulates was bimodal, with two peaks in the bins of < 0.7 μm and 4.7–5.8 μm. Dry deposition per unit area of HgP was estimated to be 47.2 μg m−2 using meteorological conditions and a size-resolved particle dry deposition model. This was 16.5% less than mercury wet deposition. Compared to HgP in fine particles, HgP in coarse particles contributed more to the total dry deposition due to higher deposition velocities. Negative correlation between precipitation and the HgP concentration reflected the effect of scavenging of HgP by precipitation.